Measuring the Inducible, Replication-Competent HIV Reservoir Using an Ultra-Sensitive p24 Readout, the Digital ELISA Viral Outgrowth Assay - Stuelke, Erin L.; James, Katherine S.; Kirchherr, Jennifer L.; Allard, Brigitte; Baker, Caroline; Kuruc, Joann D.; Gay, Cindy L.; Margolis, David M.; Archin, Nancie M. (Frontiers in Immunology, 2020)
Quantifying the inducible HIV reservoir provides an estimate of the frequency of quiescent HIV-infected cells in humans as well as in animal models, and can help ascertain the efficacy of latency reversing agents (LRAs). The quantitative viral outgrowth assay (QVOA) is used to measure inducible, replication competent HIV and generate estimations of reservoir size. However, traditional QVOA is time and labor intensive and requires large amounts of lymphocytes. Given the importance of reproducible and accurate assessment of both reservoir size and LRA activity in cure strategies, efforts to streamline the QVOA are of high priority. We developed a modified QVOA, the Digital ELISA Viral Outgrowth or DEVO assay, with ultra-sensitive p24 readout, capable of femtogram detection of HIV p24 protein in contrast to the picogram limitations of traditional ELISA. For each DEVO assay, 8-10 x 106 resting CD4+ T cells from aviremic, ART-treated HIV+ participants are plated in limiting dilution and maximally stimulated with PHA, IL-2 and uninfected allogeneic irradiated PBMC . CD8-depleted PHA blasts from an uninfected donor or HIV-permissive cells (e.g. Molt4/CCR5) are added to the cultures and virus allowed to amplify for 8-12 days. HIV p24 from culture supernatant is measured at day 8 by Simoa (single molecule array, ultra-sensitive p24 assay) confirmed at day 12, and infectious units per million CD4+ T cells (IUPM) are calculated using the maximum likelihood method. In all DEVO assays performed, HIV p24 was detected in the supernatant of cultures as early as 8 days post stimulation. Importantly, DEVO IUPM values at day 8 were comparable or higher than traditional QVOA IUPM values obtained at day 15. Interestingly, DEVO IUPM values were similar with or without the addition of allogeneic CD8-depleted target PHA blasts or HIV permissive cells traditionally used to expand virus. The DEVO assay uses fewer resting CD4+ T cells and provides an assessment of reservoir size in less time than standard QVOA. This assay offers a new platform to quantify replication competent HIV during limited cell availability. Other potential applications include evaluating LRA activity, and measuring clearance of infected cells during latency clearance assays.